Failure analysis on the oxygen corrosion of the perforated screens used in a gas injection huff and puff well. (January 2021) - Fan, Lei; Gao, Yuan; Yuan, Juntao; Yin, Chenxian; Fu, Anqing; Zhao, Mifeng; Li, Yan; Suo, Tao; Du, Xiaoyi; Wang, Yanhai
Highlights: O2 is brought into the well during the injection of N2, resulting in oxygen corrosion. The serious corrosion is resulted in O2 by greatly promotes the cathodic process. The perforated screen failed because of the serious oxygen corrosion. Abstract: The perforated screens of a gas injection huff and puff well broke down in an oilfield in western China. The physical and chemical properties of the failure-perforated screens met the requirements of relevant technical protocols. The injected gas was nitrogen produced by the membrane nitrogen method, which contains approximately 5% O2 . Therefore, a substantial amount of O2 entered the well during the gas injection, and greatly promoteed the cathodic process of the electrochemical corrosion. High salinity formation water, especially with large amounts of Cl -, further accelerated the corrosion. The significant oxygen corrosion under the well finally led to the failure of the perforated screen.